In-silico Prediction of the Beta-carboline Alkaloids Harmine and Harmaline as Potent Drug Candidates for the Treatment of Parkinson’s disease - Banerjee, Rumpa; Kumar, Mukesh; Gaurav, Isha; Thakur, Sudha; Thakur, Abhimanyu; Singh, Kunal; Karak, Sanchari; Das, Rajeswar; Chhabra, Mohit (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2021)
Background: Parkinson’s disease (PD) is a progressive neurodegenerative disease manifested by core symptoms of loss of motor control and postural instability. Loss of dopaminergic neurons is the cause of PD, thus enhancing dopamine level by pharmacological treatment is one of the key treatment strategies for PD. However, the limitations of current treatment strategies open the possibility of novel drug candidates for the treatment of PD. Objective: To investigate the anti-PD potential of Harmine and Harmaline. We aim to evaluate the therapeutic potential of Harmine and Harmaline by in-silico approaches; molecular docking, pharmacokinetic and Prediction of Activity Spectra for Substances (PASS) analysis were used for evaluating the therapeutic potential of Harmine and Harmaline and standard drug levodopa (L-DOPA). Methods: Auto dock vina was used for molecular docking of all three compounds against D2- and D3- dopamine receptors. The pharmacokinetics (PKs) and toxicity profile were predicted by pkCSM, and the pharmacological activity was predicted by PASS analysis. Results: Molecular docking showed a higher binding affinity of Harmine and Harmaline as compared to L-DOPA, and these results were supported by in-silico pharmacokinetic and toxicity profiling. Moreover, PASS analysis showed anti-PD activity of Harmine and Harmaline. Conclusion: Harmine and Harmaline exhibit higher binding affinity towards D2- and D3- dopamine receptors compared to L-DOPA, and PKs and toxicity profile support their potential as drug candidates for PD therapy.
Keywords: neurodegenerative disease